Organic materials for rechargeable batteries - Chiow, Matthew Chong How (2019)
Nanostructured conjugated polymers are a type of electrochemically active organic material with high electronic conductivity, good electrochemical stability, and superior flexibility. With these advantages, many types of research have been focused on the use of nanostructured conjugated polymers as green and renewable resources for potential high-performance energy storage and conversion devices. In overview, the procedures and methods to prepare and evaluate materials for electrochemical cells in battery research in the laboratory include cell fabrication. This Review discusses the development of current nanostructured conjugated polymers used in this experiment and how it is made into electrode materials for rechargeable batteries. In particular, the theory, and experimental procedures the results of the performance of the current material are included in this Review.